Diagnostic Accuracy of Magnetic Resonance Imaging for Detection of Anterior Cruciate Ligament Tears Taking Arthroscopy as Gold Standard (Medical Forum Monthly, 2020)
Objective: To assess the diagnostic accuracy of magnetic resonance imaging for detection of anterior cruciate ligament tears taking arthroscopy as gold standard.Study Design: Cross sectional studyPlace and Duration of Study: This study was conducted at the Department of Radiology, Lahore General Hospital, Lahore from six months 1.7.2019 to 31.12.2019.Materials and Methods: 100 patients referred to Radiology Department, with knee injury were enrolled in the study. Written informed consent was taken. Demographic detail was also noted. Then all patients underwent MRI by using 1.5 tesla and 3 tesla MRI machines. Then arthroscopy was done and patients were confirmed as positive or negative for ACL tear.Results: The mean age of patients was 52.31±11.02 years. There were 69 (69%) males and 31 (31%) females. Out of 100 cases, left side was involved in 22 cases, right side in 67 cases while 11 had bilateral injury. There were 51 cases who presented after road accident, 39 fall from height while 10 had fight. The mean duration of injury was 10.87±1.28hours. The sensitivity and specificity of MRI were 93.3% and 96.4% for detection of ACL tear. PPV and NPV were 95.5% and 94.6% while diagnostic accuracy was 95%.Conclusion: It is concluded that MRI is highly accurate diagnostic modality for detection of ACL tears. Now we can recommend MRI for screening of knee injuries instead of arthroscopy.